Elective neck dissection (END) and cN0 hard palate and upper gingival cancers: A National Cancer Database analysis of factors predictive of END and impact on survival. Issue 7 (23rd September 2019) - Obayemi, Adetokunbo; Cracchiolo, Jennifer R.; Migliacci, Jocelyn C.; Husain, Qasim; Rahmati, Rahmatullah; Roman, Benjamin R.; Cohen, Marc A.
Abstract: Background and Objectives: The reported risk of nodal metastasis in hard palate and upper gingival squamous cell carcinoma (SCC) has been inconsistent with inadequate consensus regarding the utility of neck dissection in the clinically negative (cN0) neck. Materials and Methods: Using the National Cancer Database, cN0 patients diagnosed with SCC of the head and neck with the subsites of the hard palate and upper gingiva were identified from 2004 to 2014. Results: A total of 1830 patients were identified, and END was performed on 422 patients with cN0 tumors. Pathologically positive nodes occurred in 14% (59/422) of patients in this cohort. Higher tumor stage, academic hospital type, and large hospital volume (>28 cancer‐specific cases/year) were associated with a higher likelihood of END both in univariate and multivariate analyses ( P < .05). Patients >80 years of age were less likely to receive END on multivariate analysis (OR 0.52, 0.32‐0.84). No variables, including advanced T stage, predicted occult metastases. Cox proportional hazards regression analysis showed that patients who underwent END demonstrated improved OS over an 11‐year period (hazard ratio 0.75, P = .002). On subgroup analysis, this improvement was significant in patients with both stage T1 and T4 tumors. Conclusions: Tumor stage, hospital type, and hospital volume were associated with higher rates of END for patients with cN0 hard palate SCC and after controlling for clinical factors, END was associated with improved overall survival.